Experimental evaluation of rainbow trout Oncorhynchus mykiss predation on longnose dace Rhinichthys cataractae. Issue 4 (14th August 2014) - Turek, Kelly C.; Pegg, Mark A.; Pope, Kevin L.
Abstract Laboratory and in‐stream enclosure experiments were used to determine whether rainbow trout Oncorhynchus mykiss influence survival of longnose dace Rhinichthys cataractae. In the laboratory, adult rainbow trout preyed on longnose dace in 42% of trials and juvenile rainbow trout did not prey on longnose dace during the first 6 h after rainbow trout introduction. Survival of longnose dace did not differ in the presence of adult rainbow trout previously exposed to active prey and those not previously exposed to active prey (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2n0p0680" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />χ12</alternatives> = 0.28, P = 0.60). In field enclosures, the number of longnose dace decreased at a faster rate in the presence of rainbow trout relative to controls within the first 72 h, but did not differ between moderate and high densities of rainbow trout (F2, 258.9 = 3.73, P = 0.03). Additionally, longnose dace were found in 7% of rainbow trout stomachs after 72 h in enclosures. Rainbow trout acclimated to the stream for longer periods had a greater initial influence on the number of longnose dace remaining in enclosures relative to those acclimated for shorter periods regardless of rainbow trout density treatment (F4, 148.5 = 2.50, P = 0.04). More research is needed to determine how predation rates will change in natural environments, under differing amounts of habitat and food resources and in the context of whole assemblages. However, if rainbow trout are introduced into the habitat of longnose dace, some predation on longnose dace is expected, even when rainbow trout have no previous experience with active prey.